Gene expression in Longissimus dorsi and liver in two stages of growth in pigs - Lemus-Flores, Clemente (2024)
Introduction. Gene expression varies in relation to the physiological stage of the pig and the nutritional source, and that it differs between muscle and liver. Objective. To identify genes with differential gene expression in pig biological processes in Longissimus dorsi and liver tissues, by means of transcriptome analysis, during growth (55 ± 1.05 kg) and final fattening (101 ± 7.8 kg) stages. Materials and methods. The study was conducted at the Academic Unit of Agriculture of the Universidad Autónoma de Nayarit, Mexico, during the summer of 2019. A total of twelve samples were considered, three from Longissimus dorsi muscle and three from liver per stage, for RNA extraction and sequencing. With the DESeq2 method, the gene expression of the Log2FC was obtained differentially for the growth group vs. final fattening of Longissimus dorsi and liver, and the biological function of the differentially expressed genes was identified. Results. The largest number of genes with differential gene expression was identified in the liver and on chromosome 6 in both Longissimus dorsi and liver. In Longissimus dorsi from the growth group, the genes FUT1, SESN2 and FGF21, associated with growth, were identified with high expression. Genes with low expression, such as NR4A3, PDK4, PER1 and PTPRO, involved in immune system processes and circadian rhythm, were also identified. In the liver of the growth group, the genes IHH and MYL7 were identified with high expression, while genes with low expression, including MFSD2A, LIPG, THBS1, TGFB2, LTF and APOA4, were identified as those most involved in biological processes. Conclusions. In Longissimus dorsi of the growth group, the genes were related to growth, while in the final fattening group, they were associated with immunity, growth and meat quality. In the liver of the growth group, the genes were related to growth, whereas in the final fattening group, they were associated with immunity, growth, nutrient and lipid metabolism, lipoproteins and detoxification.